Molecular detection of transcriptionally active ovine papillomaviruses in commercial equine semen - Cutarelli, Anna; De Falco, Francesca; Brunetti, Roberta; Napoletano, Michele; Fusco, Giovanna; Roperto, Sante (Frontiers in Veterinary Science, 2024)
Virological evaluation was performed on equine semen to detect the presence of papillomaviruses (PVs) using droplet digital polymerase chain reaction (ddPCR) as the aim of this study was to investigate whether the sperm from asymptomatic stallions harbors ovine papillomaviruses (OaPVs). Twenty-seven semen samples were analyzed, 18 of which were commercially acquired. The remaining nine samples comprising semen and peripheral blood, were collected from nine stallions with no apparent signs of PV-related diseases during clinical examination at the Didactic Veterinary University Hospital (DVUH) of Naples. OaPV was detected in 26 semen samples. OaPV1 was the most prevalent virus infecting equine semen. OaPV1 infected 21 semen samples (~ 80.8%) and showed a high number of DNA and RNA copies per microliter. qPCR was used to detect OaPV1 DNA in the 18 semen samples. ddPCR was used to detect and quantify the expression of OaPV2, OaPV3, and OaPV4. qPCR failed to detect DNA for these genotypes. Additionally, ddPCR was used to detect the transcriptionally active OaPV1 in six blood and semen samples from the same stallion. ddPCR failed to detect any nucleic acids in OaPVs in peripheral blood samples from the three stallions. In one semen sample, ddPCR detected OaPV1 DNA but failed to detect any nucleic acid in the remaining two semen samples, and peripheral blood from the same animals of the remaining 18 semen samples was not available, OaPV1 and OaPV4 were responsible for nine and five single infections, respectively. No single infections with either OaPV3 or OaPV4 were seen.